Evaluation of Tahfidz Qur'an Program Based on Goal Oriented Evaluation to Measure Memorization Target Achievement at SDI Al Ishlah Bukittinggi - Alifa Hanazahra; Aufatus Syakira Mardhatillah; Saputri Kelana; Fakhrur Razy; Arifmiboy Arifmiboy (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Evaluating program effectiveness is an important step in ensuring that educational objectives are achieved and that program implementation contributes to the expected learning outcomes. This study evaluated the Tahfidz Qur'an Program at SDI Al Ishlah Bukittinggi using the Goal Oriented Evaluation model to measure students’ memorization target achievement. The program is designed to develop students’ Qur'anic memorization skills while fostering proper recitation, discipline, and Islamic character. A quantitative descriptive evaluation approach was employed involving Tahfidz teachers and students as respondents. Data were collected through Likert scale questionnaires developed based on six evaluation aspects: memorization achievement, recitation quality, muroja’ah practices, discipline, Tahfidz etiquette, and overall program achievement. The data were analyzed using percentage scores, mean values, and qualitative interpretation criteria. The findings revealed a high level of goal attainment, with teacher evaluations reaching 86.1% and student responses averaging 84.0%, both indicating that the program was highly effective. The highest scores were obtained in overall program achievement and Tahfidz etiquette from teachers’ perspectives (93.3%) and discipline from students’ perspectives (91.5%). Lower scores were identified in muroja’ah practices and Tahfidz etiquette, suggesting the need for greater consistency in reinforcement activities and character development. These findings indicate that the program has been successful in supporting memorization achievement, improving recitation quality, and fostering student discipline, while also highlighting specific areas requiring further enhancement. In conclusion, the Tahfidz Qur'an Program at SDI Al Ishlah Bukittinggi effectively achieved its intended objectives according to the Goal Oriented Evaluation framework, although strengthening muroja’ah implementation and character building is necessary to optimize future program outcomes.